Fatty infiltration of the minor salivary glands is a selective feature of aging but not Sjögren's syndrome. (17th November 2017) - Leehan, Kerry M.; Pezant, Nathan P.; Rasmussen, Astrid; Grundahl, Kiely; Moore, Jacen S.; Radfar, Lida; Lewis, David M.; Stone, Donald U.; Lessard, Christopher J.; Rhodus, Nelson L.; Segal, Barbara M.; Kaufman, C. Erick; et al.
Abstract: Objective: Determine the presence and assess the extent of fatty infiltration of the minor salivary glands (SG) of primary SS patients (pSS) as compared to those with non-SS sicca (nSS). Methods: Minor SG biopsy samples from 134 subjects with pSS ( n = 72) or nSS ( n = 62) were imaged. Total area and fatty replacement area for each glandular cross-section ( n = 4–6 cross-sections per subject) were measured using Image J (National Institutes of Health, Bethesda, MD). The observer was blinded to subject classification status. The average area of fatty infiltration calculated per subject was evaluated by logistic regression and general linearized models (GLM) to assess relationships between fatty infiltration and clinical exam results, extent of fibrosis and age. Results: The average area of fatty infiltration for subjects with pSS (median% (range) 4.97 (0.05–30.2)) was not significantly different from that of those with nSS (3.75 (0.087–41.9). Infiltration severity varied widely, and subjects with fatty replacement greater than 6% were equivalently distributed between pSS and nSS participants ( χ 2 p = .50). Age accounted for all apparent relationships between fatty infiltration and fibrosis or reduced saliva flow. The all-inclusive GLM for prediction of pSS versus non-SS classification including fibrosis, age, fatty replacement, and focus score was not significantly different from any desaturated model. In no iteration of the model did fatty replacement exert a significant effect on the capacity to predict pSS classification. Conclusions: Fatty infiltration is an age-associated phenomenon and not a selective feature of Sjögren's syndrome. Sicca patients who do not fulfil pSS criteria have similar rates of fatty infiltration of the minor SG.